Influence of Zn Injection on Corrosion of 304SS Under PWR Primary Side Conditions - Wei, Haibo; Lin, Jingwei; Liu, Zhikun; Wu, Lina; Chi, Lisheng (Frontiers in Materials, 2022)
Zinc injection in nuclear power plants has been demonstrated to have a beneficial effect on the structural materials and radiation dose rate. The surface characterization techniques and electrochemical methods are employed to investigate oxide films formed 304SS in borated and lithiated high temperature water in the presence of Zn at 553.15 K. When Zn concentration increases, the number and size of Fe-based spinel oxide in the outer layer decrease while Cr-based spinel oxide in the inner layer remains unchanged. The corrosion current density of 304SS and defect density of the oxide film decrease with increasing Zn concentration. These results conclude that corrosion resistance of 304SS is enhanced in the presence of Zn. In addition, the thermodynamic analyses on the spinel oxides were performed and the results are in good agreement with the experiment observations present in this work.